PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF COURSE REVIEW HORAY SISWA KELAS X MULTIMEDIA SMK NEGERI 1 PAKEM PADA SEMESTER GENAP TAHUN PELAJARAN 2019/2020: SMK NEGERI 1 PAKEM - IRWAN PUDJIARTO (Dewan Pendidikan Bondowoso, 2022)
The progress of a nation can be seen from the quality of education in a country. Quality education can provide opportunities for children to be able to develop all the potential that exists in them. Every child needs education as a provision to face increasingly fierce global competition. Education plays an important role in maintaining the production of quality human resources. Based on the results of the research and discussion in the previous chapter, it can be concluded that the use of the Course Review Horay (CRH) learning model can improve the mathematics learning outcomes of class X Multimedia SMK Negeri 1 Pakem. This can be seen in the following research data: 1). Learning completeness, Of the 30th students of Class X Multimedia SMK Negeri 1 Pakem the number of students who completed the pre-cycle was 46.67%, in cycle I it increased to 70.30, while in cycle II it increased to 83.33%. 2). Absorption of students, the absorption of students from 30 students of Class X Multimedia SMK Negeri 1 Pakem in the pre-cycle was 62.33%, in the first cycle it increased to 69.17%, while in the second cycle it increased to 76.83%